Monitoring of the erosion process of the gully type in the Cesamar Park in the Municipality of Palmas - TO - Faria, Ana Karla Carvalho Aragão de; Zukowski Junior, Joel Carlos; Pacheco, Flavio Augustus da Mota (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
This article aims to monitor the evolution of the erosive process of the gully type, observed in slopes and bed of water course affluent to Córrego Brejo Comprido, caused by the discharges of urban drainage network from part of the avenues LO 07 and LO 05, in the green area 304 (AVSE 33). The methodology used was to conduct on-site surveys with descriptive analysis, collection of points using GPS and the elaboration of monitoring reports. The results obtained after the monitoring identified the serious environmental problem, which is in an evolutionary and accentuated process, was also satisfactory to propose the measures of stabilization of the erosive process in the degraded area.